STRES AKADEMIK SELAMA PEMBELAJARAN JARAK JAUH PADA SISWA KELAS 8 SMP KOLESE KANISIUS JAKARTA - Henny Christine Mamahit (Psiko-Edukasi, 2021)
Academic stress is a condition of students who cannot face academic demands in the form of physical, task, role, and interpersonal demands during distance learning. The purpose of this study was to get an overview of the stress conditions of the 8th grade of Kolese Kanisius Junior High School Kanisius Jakarta. The subjects of this study were 168 students. This research is descriptive quantitative research. Research data were collected using an instrument in the form of a rating scale. The academic stress scale instrument consists of 80 valid items with a reliability of 0.966. The results showed that the level of stress in terms of the academic demands of 8th grade at Kanisius College Junior High School was in the sufficient category with a percentage of 49%. The physical demands component is in the last order with a percentage of 20.28%. The task demand component has the highest contribution which acts as a trigger for academic stress with a percentage of 38.86%.